The effect of manganese and iron on mediating resuscitation of lactic acid‐injured Escherichia coli. (19th April 2022) - Zhang, H.C.; Zhang, R.; Shi, H.
Abstract: Lactic acid can induce sublethal injury of E. coli through oxidative stress. In this study, we investigated changes in SOD activity, CAT activity, GSH production and ROS production during sublethal injury and resuscitation of E. coli . Then, the effect of manganese and iron during resuscitation were studied. Both cations (≥1 mmol l −1 ) significantly promoted the resuscitation of sublethally injured E. coli induced by lactic acid and shortened the repair time ( P < 0·05). Conversely, addition of N, N, N′, N′‐tetrakis (2‐pyridylmethyl) which is a metal chelator extended the repair time. Compared with minA, manganese and iron significantly improved SOD activity at 40, 80 and 120 min and decreased ROS production at 40 and 80 min, thereby recovering injured E. coli quickly ( P < 0·05). The deletion of sodA encoding Mn‐SOD, sodB encoding Fe‐SOD or gshA / gshB encoding GSH significantly strengthened sublethal injury and extended the repair time ( P < 0·05). It meant these genes‐related oxidative stress played important roles in the acid resistance of E. coli and recovery of sublethal injury. Therefore, manganese and iron can promote the recovery of lactic‐injured E. coli by the way of increasing SOD activity, scavenging ROS, and relieving oxidative stress. Abstract : Significance and Impact of the Study: Lactic acid is widely used in food industry and can induce sublethal injury of Escherichia coli . Sublethally injured E. coli cannot be detected using traditional plate count method and recovers physiological function under suitable condition, resulting in food poisoning. Recovery is of great importance, but study on the resuscitation mechanism of injured bacteria is limited. This study uncovered recovery mechanism of lactic acid‐injured E. coli and laid the groundwork for future development of methods to detect and control sublethal foodborne pathogens.